Gastrointestinal histoplasmosis: A case report and literature review - Hughes, Julia; Martin , Brett; Hoque, Farzana (Bangladesh Journal of Medicine, 2025)
A 33-year-old female with a history of renal transplant 18 months prior was transferred to our hospital with acute kidney injury after presenting with acute gastrointestinal symptoms. Computed tomography (CT) imaging suggested diffuse colitis. Her symptoms persisted on empiric antibiotics, and she developed hematochezia. Colonoscopy revealed discontinuous ulcers, and Histoplasma urine antigen was positive. Grocott's methenamine silver (GMS) staining of a large intestine biopsy revealed narrow-based budding yeast compatible with Histoplasma capsulatum. Itraconazole was initiated, and her symptoms improved within two days. This case demonstrates the importance of suspecting histoplasmosis in immunocompromised patients presenting with gastrointestinal symptoms. Bangladesh J Medicine 2025; 36(2): 154-157